Recommendation quality, transparency, and website quality for trust-building in recommendation agents - Nilashi, Mehrbakhsh (Elsevier, 2016)
Trust is a main success factor for automated recommendation agents on e-commerce sites. Various aspects can contribute to the development of trust toward such an agent, including perceptions about the usefulness of the recommendations, the transparency of the recommendation process, and the general quality of the website. These factors have been analyzed in isolation in the literature though. We propose and evaluate a new trust model that integrates these factors, and allows us to assess their relative importance for trust-building. We conducted empirical studies in the context of two popular e-commerce websites. The findings suggest that transparency is equally important to consumers for building trust as recommendation quality, and that general we site quality contributes to the development of trust. The findings indicate that focusing on recommendation quality may be insufficient and higher levels of adoption of the recommendations can be achieved when several trust-building factors are considered.